Institutional quality and private capital flows - Cheah, Wai Loon (2014)
Based on dynamic panel GMM analysis on 140 countries for a sample period spanning from 1984 to 2007, this thesis examines whether capital flows and it’s disaggregate components (foreign direct investment, portfolio flows and debt flows) are associated with institutional quality. At the aggregate level, institutional quality is found to be significantly and positively related to capital flows. When considering sub-components, institutional quality is more associated with foreign direct investment than portfolio flows and debt flows. The disaggregate analysis also divides institutional quality into twelve components to determine which one is the driving force for capital flows. Ten out of the twelve components are found to be significant determinants of capital flows. The ten sub-components are corruption, democratic accountability, bureaucracy, law and order, investment, external conflict, internal conflict, military in politics, religious tensions, and socioeconomic conditions. The results show that the reason why capital flows less to developing countries is because their level of institutional quality differ from developed countries. The findings reported in this thesis are robust to different measures of capital flows, institutional quality and econometrics methodology.